2004
DOI: 10.1111/j.1708-8208.2004.tb00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Function of Splinted Implants in Maxillas and Posterior Mandibles, Using Brånemark System® Tiunite™ Implants: An 18‐Month Prospective Clinical Multicenter Study

Abstract: The present clinical protocol (aiming at high primary stability) and the use of oxidized titanium implants for early functional loading in the maxilla and the posterior mandible resulted in a high implant survival rate and a favorable marginal bone level during a follow-up of 18 months. The difference in marginal bone resorption between the oxidized implants in the present study and the machined implants from a previous investigation with the same study design was not statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…This implant success rate is similar to other studies which compared anodised and machined/sandblasted implants in animal models and also in clinical studies with humans [18, 19]. Jungner et al [9] reported an overall clinical success of 98.2% in a study with 136 patients, with all cases of failed implants recorded for turned surfaces in contrast with no failure for anodised implants.…”
Section: Discussionsupporting
confidence: 85%
“…This implant success rate is similar to other studies which compared anodised and machined/sandblasted implants in animal models and also in clinical studies with humans [18, 19]. Jungner et al [9] reported an overall clinical success of 98.2% in a study with 136 patients, with all cases of failed implants recorded for turned surfaces in contrast with no failure for anodised implants.…”
Section: Discussionsupporting
confidence: 85%
“…From a review of the literature, Kwon et al [27] concluded that the marginal bone loss associated with a flat-top implant is 1.0 to 1.3 mm at 1 year post-implantation, even in the presence of an improved surface [28-30]. In contrast, the marginal bone loss with a microthread, conical seal, and platform-switched design was found to be 0.11 to 0.24 mm [17,31].…”
Section: Discussionmentioning
confidence: 99%